Evidence of conservative treatment for overuse injuries analysis of systematic reviews - Alanen, Aki-Matti; Suomalainen, Ville (2011)
Overuse injuries are common among top athletes and people who exercise regularly. Conservative, non-pharmacological methods are used widely to treat overuse injuries and there is a large body of literature, including multiple systematic reviews, evaluating different terms of treatment. This literature needs summarizing and critiquing. Objective of this study was to evaluate the effectiveness of different methods of conservative treatment on overuse injuries and to provide an analysis of systematic reviews. Published systematic reviews were identified by searching Medline, PEDro, Cochrane and Sportdiscus databases from the year 1996 to July 2010. Reference lists of identified studies were also hand searched. The assessment of quality of the reviews was performed by two individual reviewers according to a specifically designed scale for systematic reviews (Assendelft et al 1995) and only high quality reviews were included into analysis. 47 good or high quality systematic reviews or meta-anayses were included after final assessment. Based on the 47 good or high quality reviews included, no firm conclusions can be drawn on the effectiveness of conservative treatments. There is limited evidence for taping when combined with other modalities and for exercise therapy. There is also limited evidence that physical modalities are not effective with the exception for ESWT. For other interventions evidence is inconclusive because of reporting faults and heterogeneity of studies. There seems to be limited evidence in favor of exercise therapy and taping combined with other interventions in the management of overuse injuries. There is dearth of good quality evidence for the management of overuse injuries. Well conducted RCT’s are in need and developing new clinical assessment tools for diagnosing overuse injuries should be considered.